Implementation of lighting painting on Raspberry Pi & Arduino platform - Liew, Guo Liang (2015)
Compared to traditional film cameras, the emergence of the digital camera has brought greater convenience to professional photographers as well as to the common men. Digital images in digital single-lens reflex (DSLR) camera can be displayed almost immediately on the device’s LCD without having to develop films to view them. With such convenience, one can take a short walk around one’s campus or city and within minutes, he would be able to notice someone taking a photograph of something or another. While smartphones are increasingly being used as the primary photography device, DSLR remains to be the more popular choice when it comes to versatility, professional image quality and all-round usefulness. As a result, photography has become a widespread hobby for people to pick up. With the widely-available tips and tricks that are accessible online, one can learn to take high quality images fairly easily. Light painting occurs when a long exposure photograph is taken while a concentrated light source is in motion. This art form is growing in popularity, with artists and hobbyists around the world pushing the limits of painting with light. Light painting can be both highly entertaining as well as beautifully artistic. Hence, this project aims to develop a remote light painting application, which consists of a web server that is housed within a Raspberry Pi allowing users to select their desired shapes to draw and light paint remotely. Equipment such as the motorised slider is used for smooth transition for horizontal movement and Pan-Tilt head to act like airbrush to paint shape in the air remotely. This project also suggests that future work can be done to implement new features and improve the overall efficiency and stability of the remote light painting application.